Comparison of the Incidence of Fragmented QRS Complex on Electrocardiogram in Patients with Connective Tissue Disorders and Healthy Individuals - Hamna Wajid; Wajid Hussain Barki; Sidra Batool; Zoha Hashmi; Ariba Shafiq; Hijab Zainab Pirzada (Life and Science)
Objective: To compare the incidence of fragmented QRS complex in electrocardiograms in patients with connective tissue disorders compared to healthy individuals. Study Design: Cross-sectional comparative study. Place and Duration of Study: This study was conducted at the Department of Medicine, Combined Military Hospital (CMH), Multan, Pakistan from February 2024 to July 2024. Methods: A total of 30 patients aged≥ 18 years and diagnosed with various connective tissue disorders were recruited in the study group (named CTD group). Another 30 individuals aged≥ 18 years or older without any known connective tissue disorders were added to the Control group. A standard 12-lead electrocardiogram was performed for each participant at rest, and the incidences of fragmented QRS complexes were recorded. The primary outcome of the study was to compare the incidence of fragmented QRS complex in patients with connective tissue disorders compared to healthy individuals by applying the Chi-square test. Results in the CTD group were also stratified by using independent t-tests and a Chi-square test for continuous and categorical variables, respectively. A P<0.05 is considered significant in all the comparisons. Results: The mean age of study participants was 41.88±8.7. Female patients comprised 70% of the study population, and males comprised 30%. The results of the primary outcomes of the study showed that a significantly higher number of patients had a fragmented QRS complex in the CTD group compared to the Control group (56.66% vs 6.66%, respectively, P=˂0.0001). The stratification of the incidences with the clinical variables in the CTD group established its significant association with age (P=0.024) and duration of the disease (P=0.048). Conclusion: A significantly higher incidence of fragmented QRS complexes is present in patients with connective tissue disorders compared to the normal population.